Pengelolaan Zakat Produktif Berwawasan Kewirausahaan Sosial Dalam Pengentasan Kemiskinan Di Indonesia - Mansur Efendi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2017)
Productive zakat is one of effective zakat distribution model for social problem solving, particularly poverty alleviation. It needs serious effort to break up cycle of poverty. Right management of zakat productive is expected to solve the poverty problem. Recent years, social entrepreneurship has been developed in many countries. It is interesting to find correlation between social entrepreneurship and productive zakat management. Hopefully, it will find a chance of social entrepreneurship concept as an alternative model of zakat productive management in Indonesia. Further, zakat productive management with social entrepreneurship insight will be able to make independent and sustainable poverty problem solving. Keywords: productive zakat, poverty, social entrepreneurship Â  Zakat produktif merupakan salah satu model penyaluran zakat yang efektif dalam penyelesaian masalah sosial, khususnya pengentasan kemiskinan. Masalah kemiskinan masih menjadi persoalan yang perlu disikapi secara serius. Agar tujuan tersebut dapat terwujud, maka zakat produktif harus dikelola dengan tepat. Kewirausahaan sosial yang beberapa tahun terakhir sedang berkembang di beberapa negara, menarik untuk ditemukan relasinya dengan pengelolaan zakat produktif. Dengan demikian akan diketahui sejauhmana peluang konsep kewirausahaan sosial sebagai alternatif model pengelolaan zakat produktif di Indonesia. Lebih jauh, pengelolaan zakat produktif yang berwawasan social enterprenurship diharapkan mampu menyelesaikan permasalahan kemiskinan secara mandiri dan berkelanjutan. Kata kunci: zakat produktif, kemiskinan dan kewirausahaan sosial